2018
DOI: 10.1152/ajpregu.00017.2018
|View full text |Cite
|
Sign up to set email alerts
|

Ergogenic effects of beetroot juice supplementation during severe-intensity exercise in obese adolescents

Abstract: Previous studies showed a higher O cost of exercise, and therefore, a reduced exercise tolerance in patients with obesity during constant work rate (CWR) exercise compared with healthy subjects. Among the ergogenic effects of dietary nitrate ([Formula: see text]) supplementation in sedentary healthy subjects, a reduced O cost and enhanced exercise tolerance have often been demonstrated. The aim of this study was to evaluate the effects of beetroot juice (BR) supplementation, rich in [Formula: see text], on phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The main purpose of this study was to determine the effects of acute supplementation with inorganic dietary NO 3 − in the form of BRJ, on exercise tolerance and cardiometabolic health among healthy men and women with obesity. Although recent studies have been similar in scope (Beals et al, 2017;Lara et al, 2015;Lima Bezerra et al, 2019;Rasica et al, 2018), to our knowledge, this is the first to report such findings in this population. The secondary purpose of this study was to explore the potential mechanisms by which these effects might occur by separating potentially salubrious components of BRJ (inorganic dietary nitrate and antioxidants) by treatment arm.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The main purpose of this study was to determine the effects of acute supplementation with inorganic dietary NO 3 − in the form of BRJ, on exercise tolerance and cardiometabolic health among healthy men and women with obesity. Although recent studies have been similar in scope (Beals et al, 2017;Lara et al, 2015;Lima Bezerra et al, 2019;Rasica et al, 2018), to our knowledge, this is the first to report such findings in this population. The secondary purpose of this study was to explore the potential mechanisms by which these effects might occur by separating potentially salubrious components of BRJ (inorganic dietary nitrate and antioxidants) by treatment arm.…”
Section: Discussionsupporting
confidence: 74%
“…This is perhaps most important in type II muscle fibers where O 2 delivery often lags behind O 2 demand ultimately leading to oxidative inefficiency and fatigue during severe-intensity exercise (Grassi, Rossiter, & Zoladz, 2015;McDonough, Behnke, Padilla, Musch, & Poole, 2005). Indeed, a similar study by Rasica et al illustrated a reduced rate of VO 2 increase during severe-intensity exercise with BRJ supplementation, in adolescents with obesity, suggesting improved efficiency (Rasica et al, 2018). The observed improvement in exercise tolerance with BRJ during high-intensity exercise is noteworthy considering that high-intensity interval training has been shown to be a highly effective intervention for improvement in weight and health status in individuals with obesity (Fisher et al, 2015;Gillen et al, 2016).…”
Section: Notementioning
confidence: 94%
See 1 more Smart Citation
“…As for other disease conditions, a recent study also found that beetroot juice improved exercise tolerance in obese adolescents, another population with poor aerobic capacity and exercise intolerance. This study found that beetroot juice could be used to combat the early onset of fatigue associated with exercise in this population [66]. Similarly, Berry et al and Curtis et al found that beetroot juice supplementation in individuals with chronic obstructive pulmonary disease (COPD) resulted in extended exercise time during submaximal exercise, decreased resting systolic blood pressure, lowered VO2 consumption during submaximal exercise, and decreased diastolic blood pressure [67,68].…”
Section: Exercise Tolerance In Populations With Various Disease Condimentioning
confidence: 84%
“…2016; Rasica et al . 2018). The present study evaluated the effects of nitrite infusion on the canine gastrocnemius muscle, which is a markedly oxidative muscle (Maxwell et al .…”
Section: Discussionmentioning
confidence: 99%